Fraud Dalam Industri Keuangan Syariah: Eksplorasi Literatur - Erfan Muhammad; Fitri Ahmad Kurniawan; Enur Hotimah; Ahmad Hanafi (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
This study explores the literature in depth about fraud prevention in sharia-based organizations. The first section explains the impact of fraud on organizations. Then it is explained how fraud can be carried out in various ways. Next, emphasis is placed on the role of auditors in detecting fraud along with various methods that can be applied to detect fraud violations. Apart from that, it also focuses on preventing fraud as a preventive measure by building a control system. This research emphasizes sharia-based organizations, both the sharia financial industry and sharia non-profit institutions. It offers multiple perspectives from an extensive literature study together with theoretical perspectives applied in previous studies. Therefore, the discussion of this research can be used as a starting point for empirical studies.